PENERAPAN ETIKA BISNIS DALAM PEMBANGUNAN JEMBATAN KACA DI DESA KEMUNING KABUPATEN KARANGANYAR - Yulianti, Refica; Aini, Fatimah Nur; Sanjaya, Elsaryo; Rahadhini, Marjam Desma (Jurnal Ekonomi & Bisnis, 2024)
The application of business ethics in the construction of the glass bridge in Kemuning, Karanganyar, is a crucial aspect to ensure the project's success from technical, social, and environmental perspectives. This research employs a literature review method to analyze relevant business ethics principles and best practices in infrastructure development. The review findings indicate that compliance with regulations and safety standards, transparency and accountability, social and environmental responsibility, and fairness in procurement and labor processes are the four key aspects to be addressed. By implementing these principles, the glass bridge project in Kemuning can achieve sustainable success and provide optimal benefits for the local community and all stakeholders involved.